2020
DOI: 10.1021/acs.jpclett.0c01372
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Polar Surfaces of Colloidal II–VI Wurtzite Semiconductor Nanocrystals Enabled by Cation Exchange

Abstract: Polar surfaces of ionic crystals are of growing technological importance, with implications for the efficiency of photocatalysts, gas sensors and electronic devices. Creation of ionic nanocrystals with large percentages of polar surfaces is an option to improve their efficiency in aforementioned applications but is hard to be accomplished because they are less thermodynamically stable and prone to vanish during the growth process. Herein we developed a strategy that is capable of producing polar surface domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The results of EDS element mapping and the molar ratio of Zn/Cu (=0.10) demonstrated that the Cu + in Cu 1.94 S NPs were partially substituted by Zn 2+ (Figures 5 g and S10 c). In spite of numerous reports on CE reaction of shaped Cu 2− x S with Zn 2+ , [26–30, 70, 71] to the best of our knowledge, this is the first time to prepare ZnS tetradecahedral NPs and their according heterostructures enabled by CE reactions. Generally, the CE product not only preserve the morphology of the starting template, but also preserve its crystal phase.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The results of EDS element mapping and the molar ratio of Zn/Cu (=0.10) demonstrated that the Cu + in Cu 1.94 S NPs were partially substituted by Zn 2+ (Figures 5 g and S10 c). In spite of numerous reports on CE reaction of shaped Cu 2− x S with Zn 2+ , [26–30, 70, 71] to the best of our knowledge, this is the first time to prepare ZnS tetradecahedral NPs and their according heterostructures enabled by CE reactions. Generally, the CE product not only preserve the morphology of the starting template, but also preserve its crystal phase.…”
Section: Resultsmentioning
confidence: 91%
“…In most cases, the products inherit the morphology and crystal phase of the parent NP [16–19] . Among the CE templates, there has been growing attention on nonstoichiometric copper chalcogenide Cu 2− x E (E=S, Se, and Te) NPs mainly owing to their high copper ion mobility in NP lattice, variable copper vacancies as well as diverse crystal phases and morphologies, which dramatically affect the CE reaction kinetics and thermodynamics, and therefore, the production of complex nanostructures and phases [20–32] . Furthermore, the catalytic and optical properties of the CE product, such as ZnE, CdE and their according heterostructures, strongly rely on the NP morphology [29, 33–35] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, very recent reports have shown that the synthesis of hexagonal NPLs of ZnS or ZnSe is challenging to achieve by direct wet bottom-up synthetic approaches. [21][22][23] In 2009 O'Brien described the preparation of separable zinc oxide (ZnO) hexagonal single-crystal slices with a thickness of about 100 nm via a poly(ethylene glycol)-assisted chemical bath deposition. [24] Then a number of ZnO NPLs were prepared using a solvothermal approach involving controlled growth on a suitable substrate [13,14,[25][26][27][28][29][30] or by ultrasound-supported [31] and electrochemical synthesis.…”
Section: Introductionmentioning
confidence: 99%